THE FLAPPERS: A ROMANTIC AND SEXUAL REVOLUTION IN THE TWENTIES FROM THE EYES OF FITZGERALD'S BERNICE BOBS HER HAIR - Wishnoebroto Wishnoebroto (Soegijapranata Catholic University, 2002)
Most of Fitzgerald's novels and stories start as a romance of love or a fantasy of extravagant glamour in representing his characters. Bernice Bobs Her Hair, however, suggests Fitzgerald's different approach by reducing this element. Critics believe that it is simply because it is a short story, or maybe because it is more based on his personal concern about the society. Nevertheless, t is work has surprised many people that latter become Fitzgerald'5 unique characteristics in writing his fictions. Compared to other Fitzgerald's work, Bernice's settings and the interplay between its characters and the places they live are quite simple. However, this simplicity contains deceptive symbolism that replicates American culture in the twenties. Fitzgerald's unparalleled representation of Jazz Age as a time of post war's confusion as well as negative consequence of industrialism is brilliantly pictured in this story. Fitzgerald uses the twenties, the time setting of the story. as a source of imagery objects that reflects social trends and individual desires. Although he uses local and restricted settings for the action site of the story, the impression of America in the twenties can be strongly feltin this story. Such quality, the writer argues, proves the outstanding ability of Fitzgerald's fiction in picturing the story with its complexities and sophistication that crosses the barrier of time and space.